A View from Above: Using Images from Drones to Identify Insects - Workman, Megan; McCornack, Brian (My University, 2018)
The use of unmanned aircraft systems, or UAS (a.k.a. drones), in Agriculture has increased with improvements in technology. Using UAS to scout fields can decrease the amount of time spent per field, allowing more ground to be covered in a day. When using a UAS to scout for insects it is important for the data to be clear enough to make correct identification of any insect present. Changes in the altitude of the flight affect the image quality, affecting the ability to identify. With this experiment we hoped to find which altitudes allowed for correct identification of known insects. The results showed that images taken from an altitude above 4 meters will result in less than 40% correct identification. Pinpointing a key altitude for insect scouting will allow for more correct identification of insects when using UAS systems.
Keywords: Fall 2018